Regulatory Phenomena in the Glutathione Peroxidase Superfamily - Brigelius-Flohé, Regina; Flohé, Leopold (Antioxidants & redox signaling, 2020)
The selenium-containing Glutathione peroxidases (GPxs)1-4 protect against oxidative challenge, inhibit inflammation and oxidant-induced regulated cell death. GPx1 and GPx4 dampen phosphorylation cascades predominantly prevention of inactivation of phosphatases by H O or lipid hydroperoxides. GPx2 regulates the balance between regeneration and apoptotic cell shedding in the intestine. It inhibits inflammation-induced carcinogenesis in the gut but promotes growth of established cancers. GPx3 deficiency facilitates platelet aggregation likely disinhibition of thromboxane biosynthesis. It is also considered a tumor suppressor. GPx4 is expressed in three different forms. The cytosolic form proved to inhibit interleukin-1-driven nuclear factor κB activation and leukotriene biosynthesis. Moreover, it is a key regulator of ferroptosis, because it reduces hydroperoxy groups of complex lipids and silences lipoxygenases. By alternate substrate use, the nuclear form contributes to chromatin compaction. Mitochondrial GPx4 forms the mitochondrial sheath of spermatozoa and, thus, guarantees male fertility. Out of the less characterized GPxs, the cysteine-containing GPx7 and GPx8 are unique in contributing to oxidative protein folding in the endoplasmic reticulum by reacting with protein isomerase as an alternate substrate. A yeast 2-Cysteine glutathione peroxidase equipped with CP and CR was reported to sense H O for inducing an adaptive response. Most of the findings compiled are derived from tissue culture and/or animal studies only. Their impact on human physiology is sometimes questionable. The expression of individual GPxs and GPx-dependent regulatory phenomena are to be further investigated, in particular in respect to human health.